Exchange Rate Policy and Sovereign Bond Spreads in Developing Countries - Yue, Zhanwei (IMF Working Papers; Working Paper ;, 2004)
We test the hypothesis of a link between exchange rate policy and sovereign bonds. We analyze the effect of exchange rate policies on supply and credit spreads of sovereign bonds issued by developing countries. An exchange rate policy is captured by the de facto exchange rate regime and the real exchange rate misalignment. The main findings are: (1) real exchange rate overvaluation significantly increases sovereign bond issue probability and raises bond spreads; (2) spreads and the likelihood of issuing bonds depend on the exchange rate regime; (3) exchange rate misalignment under a hard peg significantly increases bond spreads; (4) in time of debt crises, exchange rate policy also greatly affects the sovereign bond market, especially through exchange rate overvaluation.